From Retirement to Reinvention: Never Too Old to Participate in Educational Technology Innovation: A Literature Review - Ismail Ismail (Universitas Muhammadiyah Enrekang, 2025)
The rapid development of educational technology demands inclusive innovation, including the involvement of the elderly as a potential resource in such innovation. The increasing population of the elderly globally encourages a new paradigm that views retirement not as the end of productivity, but as a momentum for self-reinvention to contribute to the development of educational technology. This literature review aims to examine the role of the elderly in educational technology innovation through the process of post-retirement self-reinvention and identify supporting and inhibiting factors for their involvement. The results of the study show that the elderly play a role not only as users of technology, but also as contributors of experiences and ideas that enrich digital learning innovation. Active participation of the elderly is supported by age-friendly technology training, community support, inclusive policies, and cross-generational collaboration. This involvement has been shown to improve cognitive function, psychosocial well-being, and strengthen the social networks of the elderly, while addressing the risks of isolation and the digital divide. However, major challenges such as the digital divide, age stereotypes, physical and cognitive barriers remain significant barriers to the participation of the elderly. Effective strategies to overcome these barriers include adaptive training, community mentoring, policies that support technology access, and sustainable technology-based reinvention programs. This study emphasizes the importance of a holistic approach that integrates aspects of technology, pedagogy, and learning content (TPACK) to empower the elderly in educational technology innovation. This study offers a conceptual foundation for formulating policies and programs that promote the active participation of older adults, enabling their optimal contribution to the advancement of educational technology and the enhancement of their quality of life.